A unique finding of normal aldosterone level in Bartter's syndrome - Rupesh Raina; Tushar Chaturvedi; Shyam Polaconda; Amrita Siri Mukunda; Sidharth Kumar Sethi; Vinod Krishnappa (Society of Diabetic Nephropathy Prevention, 2017)
Background: Bartter's syndrome is a rare autosomal recessive renal tubular disorder characterized by hypokalemia, hypochloremia, metabolic alkalosis, hyperreninemia and hyperaldosteronemia with normotension. Bartter syndrome has five types; type 1 (mutation in sodium/potassium chloride transporter), type 2 (mutation in voltage gated potassium channel), type 3 (mutation on chromosome 1 that encodes Barttin and makes only kidney-specific chloride channel B non-functional), type 4 ( mutation in BSND gene encoding Barttin and makes both kidney-specific chloride channels A & B non-functional) and type 5 (L125P gain in function mutation in calcium-sensing receptor). Case Presentation: A 28-year-old male was hospitalized for evaluation of nausea, vomiting, generalized weakness and persistent chronic hypokalemia. Bartter's syndrome was suspected based on clinical and laboratory evidence, however serum aldosterone level was normal. Further genetic testing confirmed the diagnosis of Bartter's syndrome type 3. Conclusions: We report a case of Bartter's syndrome type 3 with a unique finding of normal aldosterone level.